EXPLORING GLOBAL TRENDS IN RESEARCH ON E-GOVERNMENT: A BIBLIOMETRIC REVIEW - ABDULLAHI UMAR; DR. AWWAL MUHAMMAD SHAFIU; ABDULRAHMAN IBRAHIM; ABBAS SULE AHMADU (International Studies Journal)
This study provides a novel and comprehensive bibliometric analysis of global e-government research, examining 2,119 publications from Scopus (2017-2024) to map emerging themes, leading contributors, and the evolution of research on e-government services. Employing Scopus tools, Excel, and VOSviewer, the study analyzes publication patterns, citations, and collaborations across countries, institutions, and researchers. Key findings indicate steady growth in e-government research, with Asia, particularly Indonesia and China, making the largest contributions, primarily in computer science, social sciences, and business management. Universitas Indonesia emerged as the top institution, with Government Information Quarterly and Sustainability Switzerland as the most influential sources. While highlighting significant collaborative research, the study notes limited involvement from less-developed nations. Distinguishing itself from prior studies, this research offers a unique, comprehensive bibliometric mapping of the e-government literature, revealing its interdisciplinary nature and underscoring the necessity for greater global inclusivity. By synthesizing trends and patterns across a substantial body of work, this study offers a distinct perspective on the development and current landscape of e-government research, concluding that addressing regional disparities and promoting broader international collaboration are vital for maximizing its impact on public sector policy and strategic management.